3D frequency selective surfaces for structural health monitoring / \c Syaiful Anas Suhaimi. - Syaiful Anas Suhaimi (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The main aim of this research is to design and analyze the possibility of introducing the Structural Health Monitoring using 3D FSS. The main objective of the study includes ; o design passive wireless 3D FSS sensor for structural monitoring system ; to enhance the capability of 2D FSS towards 3D FSS in term of sensitivity frequency shifting for monitoring structural changes ; to evaluate the performance of SHM 3D Frequency Selective Surface as passive sensor.